HUBUNGAN POLA ASUH ORANG TUA KORBAN KONFLIK TERHADAP HASIL BELAJAR GEOGRAFI PADA SISWA SMA DI KABUPATEN ACEH TAMIANG - Munawarah, Rizki; Azis, Daska; Ruliani, . (Jurnal Ilmiah Mahasiswa Pendidikan Geografi, 2024)
Parenting is the best way that is done or taken by parents in educating, guiding, and protecting their children as a manifestation of a sense of responsibility for their children and in accordance with the norms that exist in society. Learning Outcomes are changes in students' abilities and behavior after learning, the changes that occur include cognitive, affective and psychomotor abilities and within a certain time. Parents must provide good parenting to children so that children can get good learning outcomes at school. This study aims to determine the relationship between the upbringing of parents of conflict victims on the geography learning outcomes of high school students in Aceh Tamiang District. This study uses a quantitative approach and a type of correlational research. The population in this study were students at high school in Aceh Tamiang Regency totaling 30 students. The sampling technique is the total population of 30 students. The data collection technique used in this study was a questionnaire. Data analysis techniques using simple correlation. The calculation results obtained a simple correlation of 0.19 included in the very low category with a coefficient of determination of 3.61%. The calculated value of significance shows Fcount (0.75) Ftable (4.196) at a significance level of 5% so that Ho is accepted, meaning that there is no significant relationship between the parenting style of parents of conflict victims on geography learning outcomes for high school students in Aceh Tamiang District.